Voting Transparency and Conflicting Interests in Central Bank Councils - Volker Hahn; Hans Gersbach (Deutsche Bundesbank, 2001)
This paper examines whether it is socially desirable for the individual voting records of central bank council members to be published when central bankers' preferences differ. We show that the misrepresentation of their preferences is not advantageous for central bankers although central bankers take into account the fact that they might not be re-elected. Thus, the publication of voting records is beneficial since the government can distinguish central bankers in terms of their preferences and can align the central bank council's preferences with those of the general public over time by means of its re-election decisions. – – In diesem Papier wird untersucht, ob die Veröffentlichung über das individuelle Abstimmungsverhalten von Zentralbankratsmitgliedern sozial wünschenswert ist, wenn diese unterschiedliche Präferenzen haben. Wir zeigen, dass eine falsche Darstellung ihrer Präferenzen für die Mitglieder des Zentralbankrats nicht vorteilhaft ist, auch wenn die Zentralbankratsmitglieder berücksichtigen, dass sie vielleicht nicht wiedergewählt werden. Die Veröffentlichung der Abstimmung ist somit nützlich, weil die Regierung die unterschiedlichen Präferenzen der Zentralbankratsmitglieder im Lauf der Zeit mit denen der Öffentlichkeit durch entsprechende Entscheidungen in Bezug auf die Wiederwahl von Zentralbankratsmitgliedern in Einklang bringen kann.
Keywords: 330; Zentralbank; Abstimmung; Publizitätspflicht; Präferenztheorie; Geldpolitik; Public Choice; Theorie